Interpretation of Istitha'ah in Tafsir Al-Azhar and Its Relevance to the Implementation of Indonesian Hajj Pilgrimage During the Covid-19 Pandemic - Pathur Rahman; Maulani Maulani (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
This paper explains the meaning of istitha'ah in the interpretation of al-Azhar and its relevance to the implementation of the Indonesian pilgrimage during the Covid-19 pandemic. This research is library research, using the research methodology of maudhu'I interpretation. The primary source in this research is the book of Tafsir Al-Azhar written by Haji Abdul Malik Karim Amrullah and published by the Nurul Islam Foundation Jakarta in 1982. This study found that the meaning of istitha'ah in the interpretation of al-Azhar is the provision of piety, because according to Buya Hamka the best provision is piety to Allah SWT. Therefore, the author concludes that the concept of istitha'ah offered by Buya Hamka in the interpretation of al-Azhar seems irrelevant if it is applied to the implementation of the pilgrimage during the Covid-19 pandemic, because it is not in harmony with the concept of al-maqasid al-syariah which is centered on to the five benefits, especially the benefit of the soul of Hifzh an-nafs. In addition, Buya Hamka's experience when performing the hajj pilgrimage in 1927 is also impossible to apply at this time, considering the differences in legal rules. Theoretically, this research is expected to contribute to the development of Islamic studies, especially in the field of interpretation, while practically this research is expected to provide scientific explanations to the wider community regarding the problems of implementing the Indonesian Hajj during the Covid-19 pandemic